2014
DOI: 10.17221/7797-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different forms of dietary selenium supplementation on gene expression of cytoplasmic thioredoxin reductase, selenoprotein P, and selenoprotein W in broilers

Abstract: ABSTRACT:Effects of different forms of dietary selenium (Se) supplementation on gene expression of cytoplasmic thioredoxin reductase (TrxR1), selenoprotein P (SelP), and selenoprotein W (SelW) in broilers were investigated. A total of six hundred Ross 308 broilers (1-day-old) with similar body weight were randomly divided into three groups, each of which included 5 replicates of 40 birds. These three treatments received the same basal diet with only background Se level of 0.04 mg Se/kg, supplemented with 0.15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 52 publications
2
5
0
Order By: Relevance
“…A recent trial on the toxicity of Pb revealed that Se might alleviate the downregulation of GPX4, 2 and 1, DIO1, DIO2, TXNRD2-3, selenoprotein U, I, O, M, K, W, T, S 15 Sepx1, and Sepn1 expression in chicken cartilage tissue 81,82 . Similar results with Se-yeast and SeMet as organic Se sources upregulate GSH-Px1 and TXNDR1 mRNA expression in broiler breeders compared with sodium selenite 28,83 . Furthermore, SELW1 may participate in the protective role against H 2 O 2 , oxidative stress, and metabolic pathways 84,74,82 .…”
Section: Discussionsupporting
confidence: 69%
“…A recent trial on the toxicity of Pb revealed that Se might alleviate the downregulation of GPX4, 2 and 1, DIO1, DIO2, TXNRD2-3, selenoprotein U, I, O, M, K, W, T, S 15 Sepx1, and Sepn1 expression in chicken cartilage tissue 81,82 . Similar results with Se-yeast and SeMet as organic Se sources upregulate GSH-Px1 and TXNDR1 mRNA expression in broiler breeders compared with sodium selenite 28,83 . Furthermore, SELW1 may participate in the protective role against H 2 O 2 , oxidative stress, and metabolic pathways 84,74,82 .…”
Section: Discussionsupporting
confidence: 69%
“…A recent trial on the toxicity of Pb revealed that Se might alleviate the downregulation of GPX4, 2 and 1, DIO1, DIO2, TXNRD2–3, selenoprotein U, I, O, M, K, W, T, S 15 SEPX1, and SEPP1 expression in chicken cartilage tissue [ 90 , 91 ]. Similar results with Se-yeast and SeMet as organic Se sources upregulate GPX1 and TXNRD1 mRNA expression in broiler breeders compared with sodium selenite [ 35 , 92 ]. Furthermore, SELW1 may participate in the protective role against H 2 O 2 , oxidative stress, and metabolic pathways [ 83 , 91 , 93 ], as comparable data were published in rat testes [ 94 ] and pig liver [ 67 ].…”
Section: Discussionsupporting
confidence: 53%
“…Our findings were also in agreement with those of [32] who reported that increased selenium levels had improved average daily gain in the same time there was no differences on average daily gain between nano-selenium and organic selenium in broiler chickens. The function of Se on growth rate may relate to its role in the selenoprotein P and selenoenzymes type I iodothyronine deiodinase expression, which have critical roles in the synthesis of thyroid hormones and Se transport [33]. Moreover, our results of increased growth performance with selenium methionine and nano-Se could possibly due to an increased thyroid hormone regulating the body’s energy metabolism and increased digestibility of protein [34].…”
Section: Resultsmentioning
confidence: 99%